Efficient utilization of multi-core processors and many-core co-processors on supercomputer beacon for scalable geocomputation and geo-simulation over big earth data. Issue 1 (2nd January 2018) - Lai, Chenggang; Shi, Xuan; Huang, Miaoqing
Abstract: Digital earth science data originated from sensors aboard satellites and platforms such as airplane, UAV, and mobile systems are increasingly available with high spectral, spatial, vertical, and temporal resolution data. When such big earth science data are processed and analyzed via geocomputation solutions, or utilized in geospatial simulation or modeling, considerable computing power and resources are necessary to complete the tasks. While classic computer clusters equipped by central processing units (CPUs) and the new computing resources of graphics processing units (GPUs) have been deployed in handling big earth data, coprocessors based on the Intel's Many Integrated Core (MIC) Architecture are emerging and adopted in many high-performance computer clusters. This paper introduces how to efficiently utilize Intel's Xeon Phi multicore processors and MIC coprocessors for scalable geocomputation and geo-simulation by implementing two algorithms, Maximum Likelihood Classification (MLC) and Cellular Automata (CA), on supercomputer Beacon, a cluster of MICs. Four different programming models are examined, including (1) the native model, (2) the offload model, (3) the symmetric model, and (4) the hybrid-offload model. It can be concluded that while different kinds of parallel programming models can enable big data handling efficiently, the hybrid-offload model can achieve the best performance and scalability. These different programming models can be applied and extended to other types of geocomputation to handle big earth data.